Exercise training in patients with Chronic Obstructive Pulmonary Disease. Effectiveness ten years after participation - Reis, Jéssica (2019)
Poster presented at the 2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June, 2017, Campus Egas Moniz, Monte de Caparica, Portugal.